Disproportionality analysis of upadacitinib-related adverse events in inflammatory bowel disease using the FDA adverse event reporting system - Wang, Shiyi; Wang, Xiaojian; Ding, Jing; Zhang, Xudong; Zhu, Hongmei; Fan, Yihong; Sun, Changbo (Frontiers in Pharmacology, 2025)
BackgroundUpadacitinib, a Janus kinase inhibitor, has been increasingly used over the past few years to treat moderate to severe ulcerative colitis and Crohn’s disease in patients who are insufficiently responsive or intolerant to tumor necrosis factor (TNF) antibodies, demonstrating notable clinical efficacy. The long-term safety of upadacitinib in extensive populations remains unexplored. This study evaluates upadacitinib-related adverse events (AEs) utilizing data from the US Food and Drug Administration Adverse Event Reporting System (FAERS).MethodsWe employed disproportionality analyses, including the proportional reporting ratio (PRR), reporting odds ratio (ROR), Bayesian confidence propagation neural network (BCPNN), and empirical Bayesian geometric mean (EBGM) algorithms to identify signals of upadacitinib-associated AEs for treating inflammatory bowel disease (IBD).ResultsFrom a total of 7,037,004 adverse event reports sourced from the FAERS database, 37,822 identified upadacitinib as the primary suspect drug in adverse drug events (ADEs), including 1,917 reports specifically related to the treatment of inflammatory bowel disease (IBD). The most commonly reported AEs were acne, product residue present, haematochezia, frequent bowel movements, flatulence, blood cholesterol increased, aligning with clinical trial outcomes. Notably, significant but unexpected AEs, such as rosacea, proctalgia, polyp, were also reported. Subgroup analysis indicated that the most prevalent AEs among the elderly included pulmonary embolism, cataract, and sepsis, whereas the 18–65 age group most frequently reported acne, abdominal pain, and nasopharyngitis. The median onset time for AEs related to upadacitinib was 41.00 days (interquartile range [IQR] 10–141.5 days), with the majority occurring within 3 months of treatment initiation (n = 269, 66.09%), particularly in the first month (n = 171, 42.01%).ConclusionOur findings affirm clinical observations and reveal potential new AE signals for upadacitinib, underscoring the need for prospective clinical studies to verify these results and clarify their clinical relevance. This study contributes valuable evidence for ongoing safety evaluations of upadacitinib.